2022
DOI: 10.6004/jnccn.2022.7045
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Longitudinal Coping Strategies and Outcomes in Patients With Acute Myeloid Leukemia

Abstract: Background: Patients with acute myeloid leukemia (AML) face an abrupt life-threatening illness and experience immense physical and psychological symptoms. However, no data describe how patients with AML cope longitudinally with their illness or the relationship between longitudinal coping and outcomes. Methods: We conducted a secondary analysis of longitudinal data from 160 patients with high-risk AML enrolled in a supportive care intervention trial to describe coping strategies longitudinally across the illne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…We calculated descriptive statistics, including means or medians for continuous variables and proportions for categorical variables. As in previous studies, 7 , 8 , 11 , 12 , 13 we used the median split method to dichotomize use of coping strategies in our sample, because there are no validated Brief-COPE cutoffs for low or high coping. We calculated the median scores for each of the 7 coping domains, then described the proportion of patients with a score greater than the median as “high utilizers” for each coping strategy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We calculated descriptive statistics, including means or medians for continuous variables and proportions for categorical variables. As in previous studies, 7 , 8 , 11 , 12 , 13 we used the median split method to dichotomize use of coping strategies in our sample, because there are no validated Brief-COPE cutoffs for low or high coping. We calculated the median scores for each of the 7 coping domains, then described the proportion of patients with a score greater than the median as “high utilizers” for each coping strategy.…”
Section: Methodsmentioning
confidence: 99%
“…We similarly used the median spit method to identify high utilizers of the composite variables for approach-oriented and avoidant coping. 11 , 12 Given concomitant use of approach-oriented and avoidant coping strategies, we created a categorical variable to describe overall coping. From the dichotomous variables of high use of approach-oriented and avoidant coping, we classified coping as “high use, approach-oriented only,” “high use, avoidant only,” “high use, approach and avoidant,” and “high use, neither.”…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, there are very limited data on the impact of coping styles on outcomes in non‐transplanted patients with both hematological and non‐hematological malignancies. Amonoo et al 18 . showed that approach‐oriented coping is associated with less distress and better quality of life, while avoidant coping ‐ with more distress and worse quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…17 Similarly, there are very limited data on the impact of coping styles on outcomes in non-transplanted patients with both hematological and non-hematological malignancies. Amonoo et al 18 showed that approach-oriented coping is associated with less distress and better quality of life, while avoidant coping -with more distress and worse quality of life. Lehto et al 19 showed in patients with prostate cancer, that cognitive avoidance/ denial coping is a predictor of longer relapse-free survival, whereas hopelessness predicted a shorter relapse-free time.…”
mentioning
confidence: 99%